Long‐term results of up to 12 years of over 700 cases of viscocanalostomy for open‐angle glaucoma. (1st October 2014) - Grieshaber, Matthias C.; Peckar, Clive; Pienaar, Ané; Koerber, Norbert; Stegmann, Robert
Abstract Purpose To study the safety and long‐term efficacy of classic viscocanalostomy in patients with open‐angle glaucoma (OAG) in different populations. Methods A total of 726 eyes of 726 patients from Europe or South Africa with primary OAG (POAG) and pseudoexfoliative glaucoma (PXFG) were included in this retrospective multicentre study. Complete (qualified) success was defined as an intraocular pressure (IOP) equal to or lower than 21, 18 and 16 mmHg without (with or without) medications, respectively. A failed procedure was defined if IOP was above 21 mmHg, not controllable by laser goniopuncture or medications. Results The mean IOP before surgery was 42.6 ± 14.2 mmHg for all patients, 29.6 ± 6.6 mmHg for European patients and 48.1 ± 12.9 mmHg for African patients. The follow‐up time was 86.2 ± 43.1 months. Mean IOP was 15.4 ± 3.6 mmHg at 5 years, 15.5 ± 4.4 mmHg at 10 years and 16.8 ± 4.2 mmHg at 15 years. The qualified success rate for an IOP of 21, 18 or 16 mmHg or less after 5 years was 92% [95% confidence interval (CI) 0.88–0.96], 70% (95% CI 0.63–0.77) and 43% (95% CI 0.36–0.51) in European patients, and 90% (95% CI 0.87–0.93), 77% (95% CI 0.74–0.81) and 67% (95% CI 0.63–0.72) in African patients, respectively. There was no difference between the success rate for POAG and PXFG for an IOP of 21, 18 or 16 mmHg or less at 5 years (p = 0.64, p = 0.20, p = 0.22, respectively). Laser goniopuncture was performed postoperatively on a total of 127 eyes (17.7%), lowering the pressure from 23.1 ± 1.9 mmHg to 15.0 ± 2.2 mmHg. There were no significant complications, in particular, no blebitis or endophthalmitis. Conclusion Viscocanalostomy produced a sustained long‐term reduction of IOP with a low‐risk profile in European and African patients with OAG over 12 years.